IRNSS stand-alone positioning: first results in Australia. Issue 1 (2nd January 2016) - Zaminpardaz, Safoora; Teunissen, Peter J.G.; Nadarajah, Nandakumaran
Abstract : The Indian Regional Navigation Satellite System (IRNSS) currently under development is expected to reach full operational capability before 2017. As a large part of the Australian continent lies in IRNSS's service area, it is important to gain an understanding of its navigational potential and actual positioning capabilities for Australian users. The goals of this contribution are therefore to provide insight into IRNSS, to demonstrate its current positioning performance using actual L5 pseudorange tracking data, and to analyse its expected positioning performance for when the system is fully operational. As such this contribution provides the very first results of the IRNSS stand-alone positioning capabilities over Australia.